Guidelines for Managing Stress in Working of School Administrators under Chaiyaphum Primary Educational Service Area Office 3 - Sirivirotjanakul, Teerawat; Netklang, Kant (Ratchaphruek Journal, 2021)
This research were designed to study and compare stress level in school administrator’s working, and find a way to manage stress in working of school administrators under Chaiyaphum Primary Educational Service Area Office 3. Sample were 118 school administrators. The target groups were 5 experts. The instruments were questionnaire and interview form. The statistics used for data analysis were frequency value, percentage, average, standard deviation, t-test and content analysis. The research results found that; 1) The stress level in working of school administrators in overall and each aspect were medium level. Ordering with the average from highest to lowest; 2) The comparison of stress level in working of school administrators classified by gender found that the overall and each aspects were not different. When classified according to the variable of the school size found that the overall and each aspects were statistically different at the significant level of .05; 3) The guidelines for managing stress in working of school administrators found that the executives must have a plan before implementation, work system management, creating clarity of roles and responsibilities, distributing of responsibility to each person, creating good relationships between colleagues, knowing learning and developing oneself continuously, and specifying the management structure in the organization to be suitable and knowing effective time management.